PENGARUH KARAKTERISTIK KEPRIBADIAN DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP SEMANGAT KERJA GURU SEKOLAH MENENGAH ATAS NEGERI DAN SWASTA DI KECAMATAN LANGKE REMBONG -KABUPATEN MANGGARAI - Yulius Rustam Effendi (STIPAS St. Sirilus Ruteng, 2016)
Destination development at education field in the same direction that is enhancement human resources in a way implement quality education. Therefore government should seek a system quality education implemented in school. Coordinating to achieve school success determined by competence coordination principals. In context research focused on school leadership to assess how much influence personality traits and transformational leadership style of the principal to increase spirit at work of teachers. The Population this research is the teachers on public and private Senior High School that meet the criteria the homogeneity of the population. Sampling technique use proportional random sampling.